Design Temperatures for Composite Concrete-Steel Girders: B-Case Study. Issue 1 (March 2021) - Mussa, Faten I.; Abid, Sallal R.; Tayşi, Nildem
Abstract: Long-term metrological records for Adana city, which is located in the Mediterranean region in Turkey, were facilitated in this study together with a verified finite element thermal model. The aim of this study is to investigate the sectional temperature gradients in concrete-steel composite bridge girders. Solar radiation and air temperature history of more than 50 years was used, and a practical-size typical composite bridge girder was modeled for six selected months that represent the conditions of the four seasons in Adana. The analysis showed that the behaviors of positive vertical and lateral temperature gradients in summer were completely different from those in winter, while the negative temperature gradients exhibited similar sectional distributions in all seasons. The results also showed that the maximum vertical temperature gradient occurred in summer, while the maximum lateral temperature gradient occurred in winter. The maximum positive vertical gradients occurred at the top concrete surface in summer and within the steel web in winter. For the investigated conditions, the recorded maximum positive vertical gradients in summer and winter were approximately 15.0 and 12.2 °C, respectively, while the maximum positive lateral temperature gradients in summer and winter were approximately 6.1 and 10.9 °C, respectively.